2011
DOI: 10.1111/j.1399-6576.2011.02498.x
|View full text |Cite
|
Sign up to set email alerts
|

GlideScope videolaryngoscope vs. Macintosh direct laryngoscope for intubation of morbidly obese patients: a randomized trial

Abstract: Intubation of morbidly obese patients with GS was slightly slower than with DL. The increased intubation time was of no clinical consequence as no patients became hypoxemic. Both devices generally performed well in the studied population, but the GS provided better laryngoscopic views and decreased IDS scores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(79 citation statements)
references
References 36 publications
4
68
1
3
Order By: Relevance
“…More data are available on the GlidescopeÒ (Verathon Medical Inc., Bothell, WA, USA), including intubation times and success comparable with oral fibreoptic intubation under anesthesia, 86 better views and reduced difficulty with intubation compared with the MAC 4 blade, 87 and success in the awake intubation scenario -although the success rate on first attempt was only 54%, 12% required three attempts, and 4% were failures. 88 Studies suggest that intubation times with these devices are longer than with conventional laryngoscopy in terms of statistical significance, although it is questionable whether the increase is clinically relevant.…”
Section: Airway Managementmentioning
confidence: 99%
“…More data are available on the GlidescopeÒ (Verathon Medical Inc., Bothell, WA, USA), including intubation times and success comparable with oral fibreoptic intubation under anesthesia, 86 better views and reduced difficulty with intubation compared with the MAC 4 blade, 87 and success in the awake intubation scenario -although the success rate on first attempt was only 54%, 12% required three attempts, and 4% were failures. 88 Studies suggest that intubation times with these devices are longer than with conventional laryngoscopy in terms of statistical significance, although it is questionable whether the increase is clinically relevant.…”
Section: Airway Managementmentioning
confidence: 99%
“…Andersen et al also found that the Glidescope Ò video laryngoscope provided better glottic views and lower intubation difficulty scores when compared with the Macintosh laryngoscope in morbidly obese patients. 42 While an optimal laryngeal inlet view does not necessarily translate into easier intubation, advancement of the endotracheal tube may be assisted using a guiding channel on the device or an introducer. Despite the increasing number of available airway devices, no single video laryngoscope has shown superiority for use in the obese patient; however, video laryngoscopes do provide better laryngeal visualization and should be readily available for airway management.…”
Section: Direct Vs Indirect Laryngoscopymentioning
confidence: 99%
“…ont également observé que le vidéolaryngoscope Glidescope Ò fournissait de meilleures vues de la glotte et des scores de difficulté d'intubation plus bas que le laryngoscope Macintosh chez les patients obèses morbides. 42 Bien qu'une vue optimale de l'ouverture laryngée ne se traduise pas forcément par une intubation plus facile, la progression de la sonde endotrachéale peut bénéficier de l'utilisation d'un canal guide placé sur le dispositif laryngé ou sur une bougie. Malgré le nombre croissant d'outils d'intubation disponibles, aucun vidéolaryngoscope ne s'est avéré supérieur aux autres pour l'intubation du patient obèse; toutefois, les vidéolaryngoscopes fournissent une meilleure vue laryngée et devraient être disponibles pour la prise en charge des voies aériennes.…”
Section: Choix De La Technique D'intubationunclassified
“…The 25º head-up and reverse Trendelenburg positions also facilitate visualization of the vocal cords during direct laryngoscopy. 10 Critical care units should have backup emergency airway tools such as supraglottic tubes (eg, laryngeal mask airways, King laryngeal tubes, esophageal tracheal airways or esophageal tracheal double-lumen airways) that can be inserted "blindly" as a temporary measure until a definitive airway can be established 13 ; optical and/or video laryngoscopes, which can result in fewer difficult intubations than direct laryngoscopy does 14 ; and standard cricothyrotomy kits with extra large tubes. 15 Critical care units must have these items readily available in order for practitioners to follow the guidelines in the difficult airway algorithm of the American Society of Anesthesiologists.…”
Section: A: Airwaymentioning
confidence: 99%